After positivism: New approaches to comparison in historical sociology - Reviewed by Sasheej Hegde (Sociological Bulletin: Journal of the Indian Sociological Society)
Wilson, N. H. and Mayrl, D. (Eds). After Positivism: New Approaches to Comparison in Historical Sociology. Columbia University Press, 2024, 371p. $38.00